RESPONS INCEPTISOLS TERHADAP PUPUK GUANO DAN PUPUK P SERTA PENGARUHNYA TERHADAP SERAPAN P TANAMAN KACANG TANAH - Isrun Isrun (Universitas Tadulako, 2009)
The effects of guano and P fertilizer on pH (H2O), available–P and P-uptake of Peanuts in Inceptisols were studied in a pot experiment. The experiment was carried out from August to November 2007 at the Green House of Agricultural Faculty of Tadulako University. A Randomized Block Design (RBD) in a factorial experiment was used in which each treatment was replicated three times. The first factor was guano fertilizer levels: 0 t ha-1; 7.5 t ha-1; and 15 t ha-1. The second factor was P fertilizer levels: 0 kg P ha-1; 21.85 kg P ha-1; and 43.70 kg P ha-1. The test plant used was Kelinci Variety.The result of the experiment showed that the interaction effect of guano and P fertilizer significantly increased pH (H2O), available-P and uptake-P. The highest increases of pH (H2O), available P and P uptake was found in the 15 t guano ha-1 combined with 43.70 kg P ha-1 treatment.